Upaya Meningkatkan Keterampilan Menulis Karya Ilmiah dengan Microsoft Teams - Tri Riya Anggraini; Awaluddin Awaluddin (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
Abstract: The purpose of this study was to determine how to use Microsoft Teams to improve scientific writing skills.  Preliminary results showed that the expected goals had not been achieved because there were still several problems with scientific writing skills. This study used an action research method and involved 30 students. The results showed that learning activity and scientific writing learning outcomes had increased. There was an increase in the percentage of student activity scores during the learning process. The “very active” and ‘active’ scores increased by 30%, while the “less active” and “very less active” scores decreased by 23.33%. In addition, scientific writing results also improved. This can be seen from the increase in the percentage of scores in Cycle 1 by 63.33% and a significant increase in Cycle 2 by 73.33%. Thus, the application of Microsoft Teams based on technological advances has a positive impact on the progress of the learning process.